A Multi-Transportation-Modes Optimization with Time and Cost Constrains of The Postal Delivery Service in Indonesia - Sarasi, Vita (Jurnal Manajemen Teknologi, 2003)
An optimization procedure with constraints of time and cost was applied to the postal delivery service in Indonesia involving third parties of transportation modes by using Triple Algorithm and Minimum Cost Network Flow Problem methods. Althought it is nevertheless the initial stage, the optimization has showed its capability to satisfy the delivery time standard and to reduce the transportation cost simultaneously. The procedure has given a large impact on the cost effectiveness of 46,8% in this study by optimizing the choices of the transportation routes and the third parties involved. Invention of the consignment flow route and the modes selection will be useful for the network design, the third parties selection, and delivery monitoring and tracking, particularly by integrating it to the Geographical Information System. This information is especially suitable for a multifaceted archipelago and wide-area country such as Indonesia.Â Keywords:Â Postal delivery network, transportation cost, delivery time, transportation modes, optimization